Solaris - Cameron, James, 1954-; Sanchini, Rae.; Landau, Jon.; Soderbergh, Steven, 1963-; Clooney, George; McElhone, Natascha, 1971-; Davies, Jeremy, 1969-; Davis, Viola; Tukur, Ulrich, 1957-; Andrews, Peter; Bernard, Mary Ann.; Martinez, Cliff; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2003)
On a space station orbiting the mysterious planet Solaris, terrified crew members are experiencing a host of strange phenomena, including eerie visitors who seem all too human.
Closed-captioned. Includes Spanish and French dubbed versions and subtitles in English and Spanish.
Based on the novel Solaris by Stanislaw Lem.
Special features: Commentary by Steven Soderbergh and James Cameron; Steven Soderbergh's "Making of Solaris special"; HBO "Making of" special; screenplay; trailers.
Director of photography, Peter Andrews ; editor, Mary Ann Bernard ; music, Cliff Martinez ; costume designer, Milena Canonero ; production designer, Philip Messina.
George Clooney, Natascha McElhone, Jeremy Davies, Viola Davis, Ulrich Tukur.
DVD.
Keywords: Outer space -- Exploration -- Drama; Extraterrestrial beings -- Drama; Human-alien encounters -- Drama; Life on other planets -- Drama; Video recordings for the hearing impaired; Science fiction films